Pedagogical Gestures as Interactional Resources for Teaching and Learning Tense and Aspect in the ESL Grammar Classroom. Issue 1 (27th July 2016) - Matsumoto, Yumi; Dobs, Abby Mueller
Abstract : This study investigated the functions of gesture in teaching and learning grammar in the context of second language (L2) classroom interactions. The data consisted of video‐recorded interactions from a beginner‐ and an advanced‐level grammar classroom in an intensive English program at a U.S. university. The sequences of talk‐in‐interaction selected for sequential analysis involved gestures that are used by teachers for explaining English temporal concepts, and those by students to respond to their teacher's gesture. Our analysis revealed that teachers and students repeatedly used abstract deictic gestures and metaphoric gestures in the classroom, which can become important interactional resources for instruction as well as assessment of student learning. Furthermore, students effectively used gestural catchments to demonstrate their understanding of temporal concepts and to construct interactional alignments with their teachers. These findings suggest that gesture is an important element of interactional competence for teaching and learning in L2 grammar classrooms.